Analisis Kualitas Butir Soal Asesmen Formatif Bahasa Bali pada Materi Anggah-Ungguhing Basa Bali Kelas X: An Analysis of the Quality of Formative Assessment Items in the Balinese Language on Anggah-Ungguhing Basa Bali for Grade X Students - Ni Made Silvia Putrinawa Listiana; Ni Komang Sri Krisna Dewi; Putu Ayu Paramitha Wijaya; Ursula Ajeng Silvata; Ida Bagus Putrayasa (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Formative assessment is used to monitor students’ learning progress on an ongoing basis and to provide constructive feedback for both teachers and students. In language learning, formative assessment functions as a means of evaluating the gradual process of language competence acquisition rather than merely the final learning outcomes. Therefore, item analysis is necessary to ensure the quality of the assessment instruments employed. This study aims to examine the quality of each test item in the formative assessment of the Balinese Language subject, particularly on the anggah-ungguhing basa Bali material. This research adopts a descriptive quantitative design, involving Grade X students from a senior high school in Denpasar City. The research subjects were selected using purposive sampling, consisting of 36 students from class X3. The research data were collected through documentation studies of the assessment instruments and students’ responses. The data were then analyzed using validity tests, reliability tests, item difficulty indices, discrimination power indices, and distractor effectiveness analysis. The results indicate that 80% of the test items are valid, with a reliability coefficient of 0.632, which falls into the category of moderate reliability. Most items demonstrate a medium level of difficulty, accounting for 85% of the total items. Furthermore, 50% of the items exhibit optimal discrimination power, while the distractor effectiveness shows a performance rate of 72%. Overall, the formative assessment for the Balinese Language subject on the anggah-ungguhing basa Bali material meets the criteria of a high-quality assessment instrument. Nevertheless, several problematic items still require revision to enhance assessment accuracy in future implementations. This study offers a quantitative framework that can be utilized by other Balinese Language teachers as a reference for evaluating and improving test items, while also encouraging regular item analysis to enhance the effectiveness of assessment in Balinese language learning.